The Locating Chromatic Number For Corona Operation Of Path And Cycle With Python Programming - Hamzah, Nur; Asmiati, Asmiati; Nuryaman, Aang (Journal of the Indonesian Mathematical Society, 2025)
Locating chromatic number of a graph is a concept that is still interesting today because there is no theorem or algorithm that can determine the locating chromatic number of any graph. In this research, an algorithm was created to determine the locating chromatic number for corona operation of path and cycle with Python programming.